PENERAPAN REWARD DAN PUNISHMENT SISTEM POIN UNTUK PENINGKATAN KEDISIPLINAN SISWA - Andhika, Andhika Catur Setiawan (Program Studi Bimbingan Konseling Pendidikan Islam Fakultas Tarbiyah Institut Agama Islam Ngawi, 2024)
The research was conducted with the aim to first, describe the level of student discipline and the forms of rewards and punishments in developing student discipline at SMA Negeri 1 Kedunggalar. Second, to describe the steps of reward and punishment in developing student discipline at SMA Negeri 1 Kedunggalar. Third, knowing the impact of reward and punishment in SMA Negeri 1 Kedunggalar. This research uses a qualitative research approach with descriptive type. Data collection techniques are three ways, namely: observation, interviews and documentation. The data analysis technique uses (data collection), Data Reduction (data reduction), Data Display (data presentation), and conclusions. The results of this study indicate that: First, the provision of rewards and punishments carried out at SMA Negeri 1 Kedunggalar has been running well. The form of rewards given in the form of positive points, certificates, and announced in the forum. The form of punishment given is in the form of negative points, and expulsion. Second, the provision of rewards and punishments in daily activities runs well in accordance with the regulations in the student order book and refers to the four stages in disciplining students with the existence of rules, punishments, rewards and consistency. Third, the impact of the application of rewards and punishments makes students more disciplined, namely with time discipline and regulatory discipline. Keywords: Reward and Punishment, Point System, Discipline